Novel convergent-divergent serpentine flow fields effect on PEM fuel cell performance. (5th October 2017) - Chowdhury, Mohammad Ziauddin; Akansu, Yahya Erkan
Abstract: A new design of convergent and divergent flow fields are being developed in single serpentine flow field pattern for proton exchange membrane (PEM) fuel cell. The channel depth is varied by means of inclination from inlet to outlet of the bipolar plate. By the varying inclined channel depth, it created convergent/divergent flow effect along the channel length in the single serpentine. Four different convergent flow fields are manufactured by the varying inclined channel depth from inlet to outlet as 1.5 mm–0.5 mm, 2.5 mm–1.5 mm, 3 mm∼1 mm and 3.5 mm–0.5 mm, which are divergent flow fields as well by interchanging between inlet and outlet section. These convergent and divergent flow fields are compared with two conventional single serpentine having 1 mm and 2 mm constant channel depth for an active area of 4.7 cm 2 . The experimental results showed that both convergent and divergent flow fields outperforms the conventional serpentine flow fields where maximum performance was achieved from convergent flow field C1 (1.5 mm–0.5 mm) improving 19–27% power than two conventional serpentine flow fields. Therefore this novel convergent serpentine flow field effect can improve PEM fuel cell performance by its suitable bipolar plate design. Highlights: Channel depth varied by inclination along channel path. Novel Convergent-Divergent serpentine flow field patterns is developed. Current density is relatively higher in Convergent flow fields. 19–27% power increased in specific convergent flow field.